Thiamin Status in Adults Receiving Chronic Diuretic Therapy Prior to Admission to a Medical Intensive Care Unit: A Pilot Study. (15th January 2019) - Gundogan, Kursat; Akbudak, Ismail Hakki; Bulut, Kadir; Temel, Sahin; Sungur, Murat; Guven, Muhammet; Dave, Nisha J.; Griffith, Daniel P.; Ziegler, Thomas R.
Abstract: Background: The aim of the study was to determine serum thiamin concentrations in critically ill medical patients who required chronic diuretic drug treatment before admission to a medical intensive care unit (ICU). Methods: This prospective study was performed in a medical ICU. Subjects who received diuretic drug therapy for at least 6 months prior to ICU admission constituted the diuretic group. The control group was clinically matched adults admitted to the same ICU but without a history of diuretic therapy. Results: A total of 50 subjects were included (25 subjects in each of the diuretic and control groups). In the diuretic group, daily dose of furosemide prior to admission was 40 mg/d (range of 20–160 mg/d). In all subjects, the ICU admission baseline blood thiamin concentrations were 31.2 ± 27.1 ng/mL. In the diuretic group, the baseline whole blood thiamin level was significantly lower compared with levels in the control group (15.5 ± 10.7 vs 46.8 ± 29.5 ng/mL; P < 0.001). On day 2 after entry, thiamin levels remained low (23.2 ± 15.4 ng/mL in the diuretic group vs 49 ± 38 ng/mL in the control group; P = 0.003). Low thiamin levels were found in 96% of patients at baseline and in 72% of patients on the second day in the diuretic group. Conclusion: Adults receiving chronic diuretic therapy and then requiring medical ICU care commonly exhibit thiamin depletion on admission to the ICU and during the initial days of ICU care.